URBAN FORM AND CULTURAL SYMBOLISM IN RELIGIOUS GATHERINGS – A CASE OF KUMBH MELA - Udachan, Vishwa (Cuestiones de Fisioterapia, 2025)
The Kumbh Mela, recognized as one of the world’s largest religious gatherings, demonstrates the profound connection between urban form and cultural symbolism. This study examines how the festival’s temporary cityscape accommodates millions of pilgrims while reflecting sacred cosmological principles and cultural heritage. Through a multidisciplinary approach combining spatial analysis, ethnographic research, and literature synthesis, the research highlights key elements such as grid layouts, concentric zoning, and architectural features like ghats and pontoon bridges. These features are intricately aligned with the sacred geography of the Triveni Sangam, embodying the cultural cosmology of the event. The festival’s spatial organization not only addresses logistical needs but also facilitates rituals such as bathing, processions, and discourses, fostering a deep connection between physical spaces and intangible practices.The findings reveal how temporary urban environments can serve as functional and symbolic spaces, blending sacred traditions with innovative urban design principles. By integrating natural and built elements, the Kumbh Mela illustrates the balance between ecological sustainability and spiritual significance. This study provides valuable insights into creating urban environments that preserve cultural identity while adapting to modern challenges, offering a framework for designing spaces that harmonize functionality with the spiritual and cultural values of diverse communities.